Model Pengembangan Organisasi Burners Di SDN 43 Dadok Tunggul Hitam - Fahma Hakim (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
In the era of globalization and rapid technological advancement, educational institutions are required to continuously adapt to remain relevant and effective. This study aims to analyze the implementation of Burnes’ Organizational Development Model at SDN 43 Sakura Dadok Tunggul Hitam, Padang City, as well as to identify its supporting and inhibiting factors and its impact on the school’s organizational effectiveness. The research employed a descriptive qualitative approach using in-depth interviews, direct observation, and document analysis. The findings reveal that the application of Burnes’ model followed three key phases—unfreezing, changing, and refreezing— implemented through open communication and active participation among teachers and staff. These processes resulted in improved administrative efficiency, collaboration, and reflective culture within the school. From these findings, a new conceptual framework was developed, namely the Model of Sustainable Relational Adaptation (MARB), which integrates three interrelated dimensions: structural, cognitive, and relational. Theoretically, this study extends Burnes planned change theory by emphasizing the importance of social relationships and reflective learning in the context of Indonesian educational organizations. Practically, it provides recommendations for school leaders to adopt participatory leadership that fosters a collaborative and innovative school culture.